2009
DOI: 10.2298/sarh0908409s
|View full text |Cite
|
Sign up to set email alerts
|

General characteristics of adolescent sexual behavior: National survey

Abstract: It could be postulated that biological influence on sexual behaviour is powerful and resistant to the influence of time and place, as well as socio-cultural religious influences. A high rate of premarital sexual activity with a number of sexual partners, a relatively low rate of condom use and the fact that 4% of the female adolescents in this sample had an induced abortion suggest that there are gaps in the education provided to adolescents about sexual and reproductive risks within the Serbian speaking terri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
2
9
0
2
Order By: Relevance
“…In the study performed by Stankovi et al 22 , most of girls have sexual activities at the age of 17.9. The majority of our respondents had the first sex at the age of 19.…”
Section: Discussionmentioning
confidence: 96%
“…In the study performed by Stankovi et al 22 , most of girls have sexual activities at the age of 17.9. The majority of our respondents had the first sex at the age of 19.…”
Section: Discussionmentioning
confidence: 96%
“…There is no precise information about interruptions of pregnancies of adolescents because of the lack of information, so there is no precise information about pregnancy rate. According to the official information, the rate of interrupted pregnancy of females aged from 15 to 19 years was 4.1 per 1000 during the year 2006, and according to information of the Republic Institute for Statistics, pregnancy rate was 21.0 per 1000 (18).…”
Section: R E P R O D U C T I V E H E a L T H O F Y O U T H I N S E R mentioning
confidence: 99%
“…More than a quarter of adolescents in developing countries reported that they had sex before the age 15, and 21-64% of youth (15)(16)(17)(18)(19) (6). In the Balkans, 41.3% of boys and 20.8% of girls have already experienced sexual intercourse.…”
Section: R E P R O D U C T I V E H E a L T H O F Y O U T H I N T H E mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Young people in Serbia start to have sexual intercourses early in life, (84%) of boys and 65% of girls aged 13 to 25 years were sexually active. 10 In the Republic of Serbian, 11,8% of adolescents aged 16 to 18, had sexual relations, of which 4,9% with multiple partners. 11 The results of the National Population Health Survey in Serbia (2006), one in three young people (33,6%), aged from 15 to 19, applied unreliable methods of contraception, such as infertile days and ended the relationship.…”
Section: Introductionmentioning
confidence: 99%